Study of biosorption of rare earth metals (La, Nd, Eu, Gd) by Sargassum sp. biomass in batch systems: Physicochemical evaluation of kinetics and adsorption models - Oliveira, R. C. [UNESP]; Garcia, O. [UNESP] (Trans Tech Publications, 2009)
This work evaluated kinetic and adsorption physicochemical models for the biosorption process of lanthanum, neodymium, europium, and gadolinium by Sargassum sp. in batch systems. The results showed: (a) the pseudo-second order kinetic model was the best approximation for the experimental data with the metal adsorption initial velocity parameter in 0.042-0.055 mmol.g -1.min-1 (La < Nd < Gd < Eu); (b) the Langmuir adsorption model presented adequate correlation with maximum metal uptake at 0.60-0.70 mmol g-1 (Eu < La < Gd < Nd) and the metal-biomass affinity parameter showed distinct values (Gd < Nd < Eu < La: 183.1, 192.5, 678.3, and 837.3 L g-1, respectively); and (c) preliminarily, the kinetics and adsorption evaluation did not reveal a well-defined metal selectivity behavior for the RE biosorption in Sargassum sp., but they indicate a possible partition among RE studied. © (2009) Trans Tech Publications.
Keywords: Biosorption; Physicochemical modeling; Rare earth metals; Sargassum sp.; Adsorption model; Batch systems; Best approximations; Biosorption process; Experimental data; Initial velocities; Langmuir adsorption model; Metal adsorption; Metal selectivity; Metal uptake; Physicochemical model; Pseudo-second-order kinetic models; Sargassum sp; Adsorption; Biomass; Europium; Gadolinium; Lanthanum; Metals; Neodymium; Rare earths; Metal recovery